China's education aid to Africa : fragmented soft power - Ye, Wei (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"China's emergence as an aid donor in Africa has caught global attention, with China's activity being viewed as the projection of soft power of a neo-colonialist kind in an international relations context. This book, which focuses on China's education aid -- government scholarships, training, Confucius Institutes, dispatched teachers, etc. -- reveals a much more complicated picture. It outlines how the divide between the Chinese Ministry of Commerce and the Ministry of Education hinders China's soft power projection, how much of China's aid is bound up with an education-for-economic-growth outlook, mirroring China's own recent experiences of economic development, and how China's aid, prioritized to reflect the commercial sector's interests, is out of step with most international development aid, which is dominated by education agendas and the campaigns of international organizations and traditional donors, which leaves China easily exposed to the charge of neo-colonialism. It emphasizes the international development cooperation architecture as an open system by which both traditional donors and Southern countries transform"--
Keywords: Educational assistance, Chinese -- Africa; China -- Foreign economic relations -- Africa; Africa -- Foreign economic relations -- China; SOCIAL SCIENCE / Ethnic Studies / General; SOCIAL SCIENCE / Research